Serum Adiponectin Levels and Their Association with Age, Gender and Waist Circumference: Insights from a Cross-Sectional Study: Serum Adiponectin Levels and Age, Gender, Waist Circumference - Humayun, Zunaira; Zaidi, Mehreen; Farooq, Hera; Shayan, Shahram; Asad, Alia; Ramzan, Shazia; Chaudhary, Zoraiz; Muhammad, Tahir; Maqbool, Tahir; Hadi, Faheem (Pakistan Journal of Health Sciences, 2025)
Adipose tissue secretes the adipokine adiponectin, which is essential for insulin sensitivity, cardiovascular health, and metabolic control. Although prior studies suggest that age and waist circumference (WC) influence adiponectin levels, contradictory results indicate the need for further research. Objectives: To evaluate and compare serum adiponectin levels among individuals of different age groups and waist circumference categories. Methods: A cross-sectional study was conducted with 50 individuals. Age, WC, body mass index (BMI), and gender were among the anthropometric information gathered. Spearman's correlation was used to test serum adiponectin levels and their relationships with these factors. The threshold for statistical significance was p<0.05. Results: The average amount of adiponectin in the blood was 5.59 ± 1.94 ng/mL. Adiponectin did not significantly correlate with either WC (r=+0.17, p=0.16) or age (r=-0.06, p=0.60). Furthermore, although somewhat higher in females, adiponectin levels did not significantly correlate with either gender (p=0.47) or BMI (r=+0.10, p=0.37). Conclusion: It was concluded that results show no significant relationships of adiponectin with WC, in contrast to previous research that found an inverse link with WC or an age-related increase in adiponectin. This could be the result of unmeasured confounding variables, including food and lifestyle, sample size restrictions, or demographic characteristics. More extensive research is needed to elucidate these connections and investigate adiponectin's potential as a biomarker for metabolic diseases.